Land utilization of hydroelectric power from Koto Panjang reservoir becoming a tourist destination in Kampar District, Riau Province - Abdul Rahman Cemda (Indonesian Journal Education, 2026)
This study examines land utilization of the Koto Panjang Hydroelectric Power Reservoir as a tourist destination in Kampar Regency, Riau Province, with an emphasis on sustainable tourism development. A qualitative descriptive approach was employed through field observations and in-depth interviews to capture existing land-use practices, tourism activities, and stakeholder perceptions. The findings reveal that the reservoir possesses significant tourism potential, particularly in scenic-based tourism supported by natural landscapes, reservoir waters, and surrounding forest areas. However, current utilization remains suboptimal, with limited development in water tourism, culinary attractions, and resting facilities. Furthermore, tourism development faces challenges related to environmental degradation, weak governance, and conflicts with the reservoir’s primary function as a hydropower and water resource system. From a sustainability perspective, tourism utilization has not fully achieved a balance between economic benefits, social acceptance, and ecological preservation. This study concludes that tourism development in the Koto Panjang Reservoir should prioritize ecotourism-based scenic tourism, strengthen community participation, and integrate environmental protection to support sustainable regional development without undermining the reservoir’s core functions.